Insecure prosperity : small-town Jews in industrial America, 1890-1940 - Morawska, Ewa T. (Princeton University Press, 1996)
"This captivating story of the Jewish community in Johnstown, Pennsylvania reveals a pattern of adaptation to American life surprisingly different from that followed by Jewish immigrants to metropolitan areas. Although four-fifths of Jewish immigrants did settle in major cities, another fifth created small-town communities like the one described here by Ewa Morawska. Rather than climbing up the mainstream education and occupational success ladder, the Jewish Johnstowners created in the local economy a tightly knit ethnic entrepreneurial niche and pursued within it their main life goals: achieving a satisfactory standard of living against the recurrent slumps in local mills and coal mines and enjoying the company of their fellow congregants. Rather than secularizing and diversifying their communal life, as did Jewish immigrants to larger cities, they devoted their energies to creating and maintaining an inclusive, multipurpose religious congregation."--